2018
DOI: 10.3390/fire1030044
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire Impact and the “Fire Paradox” in a Natural and Endemic Pine Forest Stand and Shrubland

Abstract: Fire is a powerful force that has shaped forests for thousands of years. It also provokes widespread social concern due to possible economic damage, social effects, impact on homes and properties, and other social effects including fatalities. Regions with seasonal variations in aridity have a fire regime dependent on climate resulting from the role of precipitation and temperature in fire occurrence, implying a synchrony of fire occurrence at regional scale. This spatial and temporal variation of fire regimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Throughout this paper the Safe Development Paradox shall refer to all three keyphrases for the process described. Even outside of flood risk, structural measures are often used to mitigate natural hazards with similar challenges in tackling the Safe Development Paradox: strengthening infrastructure in earthquake zones [12]; larger dams for avalanches [13]; stronger housing design in tornado zones [14]; and the fire paradox, whereby preventing forest fires against a steady increase in fire risk and subsequent wildfire damage [15], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout this paper the Safe Development Paradox shall refer to all three keyphrases for the process described. Even outside of flood risk, structural measures are often used to mitigate natural hazards with similar challenges in tackling the Safe Development Paradox: strengthening infrastructure in earthquake zones [12]; larger dams for avalanches [13]; stronger housing design in tornado zones [14]; and the fire paradox, whereby preventing forest fires against a steady increase in fire risk and subsequent wildfire damage [15], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…While fire suppression has led to a significant decline in global fire activity in the 20th century [28], it has been suggested that fire suppression may lead to a paradox: the more effective the fire suppression, the more severe future fires [29][30][31][32]. This is known as the wildfire paradox [33].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, fire suppression can lead to larger fires by increasing fuel load and continuity. Specifically, the prolonged absence of wildfires may result in the significant accumulation of combustible biomass, such as dead wood, that should have been periodically burned [29][30][31][32], along with vegetation encroachment [38], especially in regions lacking fire prevention measures [39]. Over time, the increase in fuel load can create conditions for more intense fires.…”
Section: Introductionmentioning
confidence: 99%
“…This term, in business, describes a "quick-fix" management strategy, which focuses on fixing rather than preventing problems, often resulting in unintended negative consequences [18]. In the realm of forest fire management, such a strategy can initially appear successful as it is likely to reduce damage in the short term, but in the long term it fails to address the roots of the increasing wildfire potential [19] resulting in the so-called "fire paradox" [20,21]. This problem has been documented clearly and current scientific thinking calls for shifting the focus from fire suppression to mitigation, prevention, and preparation, as such a policy is more likely to reduce the negative socioeconomic and ecological effects of fire than the current, largely one-dimensional, focus on fire exclusion [22].…”
Section: Introductionmentioning
confidence: 99%